Comparative assessment of carbon dioxide (CO2) absorption capacities in Koompassia malaccensis and Hopea nervosa in Tekam Forest Reserve, Pahang, Malaysia - HASYA HANNANI RUZIMAN; AZIAN MOHTI; NURUL EMYLIANA SYAFIKA CHE YO; FAEZAH PARDI (Nusantara Bioscience, 2024)
Abstract. Ruziman HH, Mohti A, Yo NESC, Pardi F. 2024. Comparative assessment of carbon dioxide (CO2) absorption capacities in Koompassia malaccensis and Hopea nervosa in Tekam Forest Reserve, Pahang, Malaysia. Nusantara Bioscience 16: 185-191. Trees, the dominant life form in forests, are essential in the functioning of the terrestrial biosphere, especially for the carbon cycle of the ecosystem. This study aims to assess CO2 absorption by two forest production species: Koompassia malaccensis Maingay and Hopea nervosa King. The experiment was carried out in an acrylic box, and the variation of carbon dioxide concentration, humidity, light, and temperature was measured using a Carbon Dioxide, Light, Temperature, and Humidity (CLTM) sensor. The experiment was conducted in an open area from 7:30 am to 6:30 am the next day (23 hours). The results showed that H. nervosa absorbed more CO2 (71.13 ppm/hour) than K. malaccensis (51.54 ppm/hour), thus promoting its ability to address climate change in the microenvironment. As for the relationship between carbon dioxide absorption and photosynthesis variables, both species show a positive correlation between CO2 absorption and humidity. In contrast, light and temperature were very weakly correlated to CO2. Therefore, it was identified that H. nervosa (Dipterocarpaceae) and K. malaccensis (Fabaceae) are tree species with high CO2 absorption capacity and thus can be considered suitable trees for replanting, especially in light of carbon mitigation initiatives.